Pedagogical Principles in Implementing a Data Visualization Project in an Undergraduate Public Health Informatics Course - Bautista, John Robert (Applied Clinical Informatics, 2024)
Background The Applied Public Health Informatics Competency Model lists “data analysis, visualization, and reporting” as one of the eight competencies when teaching public health informatics. Thus, public health informatics students need to develop knowledge and skills in visualizing public health data. Unfortunately, there is limited work that discusses pedagogical principles that could guide the implementation of pedagogical activities related to data visualization in public health informatics.Objective This study aimed to introduce, discuss, and reflect on pedagogical principles that were implemented for a data visualization project in an undergraduate public health informatics course.Methods A reflective teaching approach was used to guide the discussion and reflection on how pedagogical principles were implemented for a data visualization project in an undergraduate public health informatics course. The generic implementation framework (i.e., preimplementation, implementation, and postimplementation) was used to organize the discussion of the course's implementation.Results Four pedagogical principles were implemented as part of a data visualization project in an undergraduate public health informatics course: scaffolding (i.e., outputs built on top of each other), constructivism (i.e., students apply knowledge and work in teams to create a dashboard), critical consciousness (i.e., embedding social determinants of health (SDOH) in their dashboard), and equity and inclusion (i.e., using a free data visualization software that is easy to use for beginners and is used by public health institutions). Postimplementation reflection revealed areas of improvement, such as enhancing group advising, adding more SDOH variables in the dashboard, and plans for scalability.Conclusion A data visualization project in an undergraduate public health informatics course could benefit from implementing multiple pedagogical principles. Overall, creating dashboards can be a learning tool to enhance data visualization skills among undergraduate public health informatics students. Dashboards can also emphasize the impact of health disparities and inequities in public health by incorporating the principles of SDOH.
Keywords: public health; public health informatics; education; data visualization; Power BI; strategies for health IT training